A structural, electronic and electrochemical study of polypyrrole as a function of oxidation state - Warren, M.R.; Madden, J.D.
The electronic, structural, and chemical properties of polypyrrole doped with the hexafluorophosphate ion are investigated as a function of oxidation state. These properties are found to be highly correlated; specifically, they all experience a rapid transition at approximately -0.1V versus SCE. The electronic conductivity of the film changes by two orders of magnitude through the transition potential, in the well-known opinginduced metal-insulator transition. Also at -0.1V versus SCE, X-ray diffraction and macroscopic actuation measurements reveal a structural change in the polymer. Results suggest a loss of pi-stacking in the polymer crystals, and a reordering of the dopant ions in the matrix. The dopants appear to exist in an isotropic liquid-like state in the highly oxidized film, changing to a channel structure at the transition point. This change in structure is also consistent with the transition observed in the electrochemical impedance spectrum. The equilibrium charge on the polymer with oxidation state is consistent with a constant DC capacitance, however theAC impedance spectrum shows increased constant phase element behavior in the reduced state. This could be due to a greater range of diffusion constants in the reduced state, which we associate with the heterogeneous ion configuration.
Keywords: POLYPYRROLE; X-RAY DIFFRACTION; IMPEDANCE SPECTROSCOPY; METAL-INSULATOR TRANSITION